Pembentukan Karakter Disiplin Anak Usia Dini Melalui Metode Pembiasaan - Hasan, Masita; Fitri, Riskal; Nirwana, Nirwana (Ihya Ulum: Early Childhood Education Journal, 2024)
This research aims to improve the formation of discipline character in early childhood at TK A Baitul Qalbi Islamic School, Makassar City, through the habituation method. The problem identified is the low discipline of the children, such as frequently arriving late to school, not completing tasks on time, and not adhering to the established rules. This study uses the Classroom Action Research (CAR) approach with two cycles, each consisting of two meetings. In the first cycle, the habituation method was applied to instill discipline, such as arriving on time and completing tasks within the specified timeframe. In the second cycle, the habituation method was reinforced with a more consistent approach, such as giving rewards and positive reinforcement every time the children displayed disciplined behavior. Overall, the implementation of the habituation method in these two cycles successfully improved the discipline character of the children at TK A Baitul Qalbi Islamic School. Based on the results of this study, it can be concluded that consistent habituation can shape the disciplined character of early childhood, which is expected to be applied in their daily lives.